The School-based Occupational Safety and Health Management in Vocational School - Ketut Ima Ismara; Didi Supriadi; M. Riza Syifaulliya; Kitisak Keaw-aram (Universitas Sarjanawiyata Tamansiswa, 2021)
The vocational high school graduates are required to have the competence to implement Occupational Safety and Health (OSH). This study investigated the implementation of school-based Occupational Safety and Health Management in the vocational school. The OSH implementation viewed from seven principles: curriculum management, student management, educator management, facilities and infrastructure management, funding management, school and community management, and cultural and environmental management. This study is descriptive research that used subjects from 10 public vocational schools and ten private vocational schools in Yogyakarta Province. The data obtained from the Education Report Card Mapping Report Evaluation Results of the Directorate of Vocational Education at the Ministry of Education and Culture of Indonesia. The findings showed that the management of OSH in private vocational schools higher than the public one. The principle of OSH for the management of students is